Sedimentary organic carbon and nitrogen stocks of intertidal seagrass meadows in a dynamic and impacted wetland: Effects of coastal infrastructure constructions and meadow establishment time. (15th November 2022) - Casal-Porras, Isabel; de los Santos, Carmen B.; Martins, Márcio; Santos, Rui; Pérez-Lloréns, J. Lucas; Brun, Fernando G.
Abstract: Seagrass meadows, through their large capacity to sequester and store organic carbon in their sediments, contribute to mitigate climatic change. However, these ecosystems have experienced large losses and degradation worldwide due to anthropogenic and natural impacts and they are among the most threatened ecosystems on Earth. When a meadow is impacted, the vegetation is partial- or completely lost, and the sediment is exposed to the atmosphere or water column, resulting in the erosion and remineralisation of the carbon stored. This paper addresses the effects of the construction of coastal infrastructures on sediment properties, organic carbon, and total nitrogen stocks of intertidal seagrass meadows, as well as the size of such stocks in relation to meadow establishing time (recently and old established meadows). Three intertidal seagrass meadows impacted by coastal constructions (with 0% seagrass cover at present) and three adjacent non-impacted old-established meadows (with 100% seagrass cover at present) were studied along with an area of bare sediment and two recent-established seagrass meadows. We observed that the non-impacted areas presented 3-fold higher percentage of mud and 1.5 times higher sedimentary organic carbon stock than impacted areas. Although the impacted area was relatively small (0.05–0.07 ha), coastal infrastructures caused a significant reduction of the sedimentary carbon stock, between 1.1 and 2.2 Mg OC, and a total loss of the carbon sequestration capacity of the impacted meadow. We also found that the organic carbon stock and total nitrogen stock of the recent-established meadow were 30% lower than those of the old-established ones, indicating that OC and TN accumulation within the meadows is a continuous process, which has important consequences for conservation and restoration actions. These results contribute to understanding the spatial variability of blue carbon and nitrogen stocks in coastal systems highly impacted by urban development. Highlights: Seagrass organic carbon (OC) stock was impacted by coastal infrastructures. OC stocks at impacted areas were 1.5 times lower than at non-impacted areas. Non-impacted areas presented 3-fold higher percentage of mud than impacted areas. Recently established meadow presented 30% lower OC than the old-established ones.